United States of America. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in the United States of America during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as public and private corporations, as well as international alliances and financing. Likewise, work was done on banking and agricultural financial systems, on policies and programs and knowledge management, in order to identify new and emerging issues in agriculture. Finally, support was given to the attention to the damage caused by the hurricanes in the Caribbean and the control of non-communicable diseases, such as chronic kidney disease.